ISOLASI DAN PENCIRIAN LIGNIN DARI LINDI HITAM DAN SENGON UNTUK BAHAN PEREKAT - Adi Santoso; Surdiding Ruhendi; Suminar S Achmadi; Endang Suhendang (Jurnal Penelitian Hasil Hutan, 1995)
Lignin   is  the  polymer   which   has  been   degraded    and  removed    in pulping  processes.     The occurance   of lignin  as  a waste  product   in pulp  mills  has  made   it an  attractive   raw  material  for adhesives    eversince    the  beginning   of  the  sulfite  pulping   of  wood.   Therefore,    the  isolation   and its  characterization   are   important  lo  achieve    effective    lignin   removal.    In  this   investigation,  isolation   and  characterization   of black  liquor  and  sengon   lignin  were  carried  out.  the  isolation of  lignin   was   performed   by  precipitation   of  lignin   from  black   liquor   and  the  preparation   of  lignin   by way  of  cellulose   dissolution   from   sengon   (Paraserianthes    falcataria  (L) Nielsen).  the  recovery   of  lignin  was  evaluated   in  an  allempt  to  optimize  recovery    at  high  purity   by  qualitative  analyses   (ie.   UV - and  IR - spectrometry)   and  quantitative  analyses   (ie.  percentage   of pure  lignin, equivalent    weight,    ash   content,    etc).    lndulin-AT     (commercial   lignin) is  used   as   standard   of comparison.the  result   indicates   that  black   liquor   lignin   is  guayacil    lignin  with  16,8   -  17,4%   methoxyl  content,    2.0   - 2.1  %  phenolic    hydroxyl  content,    11.  7 -  11.9%     ash  content   and  percentage    of pure   lignin  about   64. 2  -  71.1   %.  this   result   is similar  with  indulin   - AT.    the   result  of sengon lignin  analyses show   that  it is syringyl   lignin  with  26.7  - 27.2%   methoxyl   content,    0.8  -  0.9% phenolic   hidroxyl   content,    25.1   - 25. 6%  ash  content  and  percentage    of pure   lignin  about  36. 1 -46.2%.   Side  effect of  these  result  were  reactivity  of sengon   lignin  is  lower  than  lignin from   black liquor and indulin - AT,  therefore,   sengon  lignin has no potential  as raw material for adhesives.